1987
DOI: 10.1111/j.1365-2125.1987.tb03103.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of nifedipine infusion in normal volunteers.

Abstract: Two studies of the pharmacokinetics and pharmacodynamics of intravenous nifedipine infusion were performed: the first, a randomised double‐ blind crossover study of nifedipine and its vehicle in eight subjects, the second a dose ranging study in nine subjects. Nifedipine pharmacokinetics did not vary with dose or duration of infusion up to 8 h, and are similar to those reported for other nifedipine preparations. Nifedipine increased heart rate and forearm blood flow and decreased blood pressure after bolus inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
2
12
1
1
Order By: Relevance
“…Nifedipine usually shows no marked antihypertensive eŠect in normal individuals, because the diastaltic sympathicotonia through pressoreceptor with decreases of peripheral arterial resistance induces the increases of heart rate, and prevents blood pressure decreases. 20) However, there have been reports [21][22][23][24][25][26][27][28] that nifedipine signiˆcantly reduced the blood pressure by oral and sublingual administration and that the serum nifedipine concentration was correlated with the antihypertensive eŠect in normal individuals. In our study, also, the serum concentration was correlated with blood pressure, especially DBP, by each administration method.…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine usually shows no marked antihypertensive eŠect in normal individuals, because the diastaltic sympathicotonia through pressoreceptor with decreases of peripheral arterial resistance induces the increases of heart rate, and prevents blood pressure decreases. 20) However, there have been reports [21][22][23][24][25][26][27][28] that nifedipine signiˆcantly reduced the blood pressure by oral and sublingual administration and that the serum nifedipine concentration was correlated with the antihypertensive eŠect in normal individuals. In our study, also, the serum concentration was correlated with blood pressure, especially DBP, by each administration method.…”
Section: Discussionmentioning
confidence: 99%
“…The effects were rather small in these normotensive volunteers, and the extent of interand intra-subject variability of the haemodynamic effects was too large to allow pharmacodynamic-pharmacokinetic modelling in the majority of the subjects. Also some haemodynamic activity of the vehicle cannot be ruled out (Walley et al, 1987). After oral administration the effects were even less and, because the study was not placebo controlled, it can only be concluded that there are no major differences between the haemodynamic effects of nitrendipine when given as a tablet as compared with an Osmet formulation.…”
Section: Calculationsmentioning
confidence: 99%
“…The side-effects were remarkably severe and consistent for one subject, whereas for the other subjects side-effects were less frequent and less severe. The local irritation after intravenous administration which is probably caused by the vehicle (Walley et al, 1987) could not completely be prevented by simultaneous infusion of normal saline, but no signs of thrombophlebitis were observed.…”
Section: Calculationsmentioning
confidence: 99%
“…Although the pharmacokinetics and pharmacodynamics of nifedipine have been characterized extensively in adults (6)(7)(8)(9), only a few studies to date have evaluated the hemodynamic responses in a pediatric population (3)(4)(5), and pharmacokinetic studies in this population are completely lacking. The objectives of this study were to determine the pharmacokinetic properties of nifedipine in children with BPD and pulmonary artery hypertension after the administration of a single oral dose of the drug, and to evaluate the relationship between plasma nifedipine concentrations and the acute responses.…”
mentioning
confidence: 99%